ACCOUNTING DIGITAL TRANSFORMATION ASSESSED THROUGH AUDITOR WORKLOAD AND EVIDENCE VERIFICATION - Shabrina Tri Asti Nasution; Thezar Fiqih Hidayat Hasibuan; Devi Ayu Putri; Desy Astrid Anindya (PT. Radja Intercontinental Publishing, 2024)
This research examines the usefulness of digital transformation in the implementation of finance in companies. Digital transformation in this case is analyzed by examining the positive influence on auditor workload and evidence verification. The data analysis method used in this research is full model Structural Equation Modeling (SEM) analysis using the Partial Least Square (PLS) approach or better known as SEM-PLS, with a statistical application known as SmartPLS, the SmartPLS version used is version. 3.2.9., the research sample was 30 auditors at a public accounting firm, The data collection used was a questionnaire instrument which was developed by the needs of researchers by examining in more detail about digital transformation after a comprehensive literature review which serves to identify and operationalize the main theoretical constructs. The research results show that digital transformation is influenced by evidence verification, but workload has no effect on digital transformation. In this way, digital transformation can verify data precisely, in real-time, portfolios and submitted documents can be checked more thoroughly.